Assisting Vitamin A Supplementation for Toddlers at Tri Jaya Posyandu, Kedungjaya, Cirebon - Winda Dwi Yanthi; Carti Mulyawati; Widianingsih; Yunus (SOCIRCLE : Journal Of Social Community Services, 2023)
Vitamin A supplementation is a routine child-health service delivered through Posyandu, yet limited cadre availability can disrupt registration, participant flow, counselling, and documentation during service days. This community service program aimed to support the delivery of vitamin A supplementation for toddlers at Tri Jaya Posyandu, RW 01, Kedungjaya Village, Cirebon Regency. The program was conducted on 6 February 2024 through a participatory partnership between Posyandu cadres and STIE Cirebon community service students. Needs were identified through preliminary observation and coordination with cadres, followed by preparation of the service flow, participant registration, assistance during age and record verification, support for the administration of age-appropriate vitamin A by authorized Posyandu personnel, and post-activity reflection. Program evaluation used attendance records, an implementation checklist, and field notes. Twenty-one toddlers participated in and completed the service process. Student involvement helped cadres organize registration, direct caregivers through the service stations, support documentation in maternal and child health records, and maintain an orderly flow despite limited cadre availability. The immediate output was a completed vitamin A service session for all attending participants and a clearer division of operational tasks between cadres and students. Because the program did not use a pretest-posttest design and did not have the total eligible-population denominator for RW 01, the findings represent process achievement rather than village-level coverage or long-term health impact. Continued cadre-led follow-up and updated target lists are recommended.